1985
DOI: 10.1093/ajcn/41.6.1210
|View full text |Cite
|
Sign up to set email alerts
|

Tea drinking and microcytic anemia in infants

Abstract: To evaluate the effect of tea drinking on the occurrence of microcytic anemia in infants, we studied 122 healthy infants who underwent routine blood counts at the age of 6-12 months. An overall high frequency of anemia (Hb less than 11 gm/dl-48.4%), microcytosis (MCV less than 70 Mm3-21.3%) and microcytic anemia (19%) was found in the whole group. The percentage of tea drinking infants with microcytic anemia (32.6%) was significantly higher than that of the non-tea drinkers (3.5%). The daily amount of tea drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 12 publications
2
33
1
1
Order By: Relevance
“…The factors that remained in the model to predict high serum ferritin concentrations were high mothers' parity, absence of recent infections, high birth weight, high energy adjusted intakes of non-haem iron, high vitamin C and low calcium intakes (Cowin et al, 2001). Two casecontrol studies (Kuvibidila et al, 1992;Merhav et al, 1985) focused on the relationship between tea consumption and the prevalence of anaemia without determining the iron deficiency status specifically with serum ferritin measurements. Both studies observed (Kuvibidila et al, 1992;Merhav et al, 1985) that anaemia, as determined by Tea consumption and iron status EHM Temme and PGA Van Hoydonck haemoglobin concentrations only, is more prevalent among tea drinking infants than among non-tea drinkers, even with a longer period of beef and poultry feeding in the tea group (Merhav et al, 1985) or adjusting for episodes of sickness (Kuvibidila et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The factors that remained in the model to predict high serum ferritin concentrations were high mothers' parity, absence of recent infections, high birth weight, high energy adjusted intakes of non-haem iron, high vitamin C and low calcium intakes (Cowin et al, 2001). Two casecontrol studies (Kuvibidila et al, 1992;Merhav et al, 1985) focused on the relationship between tea consumption and the prevalence of anaemia without determining the iron deficiency status specifically with serum ferritin measurements. Both studies observed (Kuvibidila et al, 1992;Merhav et al, 1985) that anaemia, as determined by Tea consumption and iron status EHM Temme and PGA Van Hoydonck haemoglobin concentrations only, is more prevalent among tea drinking infants than among non-tea drinkers, even with a longer period of beef and poultry feeding in the tea group (Merhav et al, 1985) or adjusting for episodes of sickness (Kuvibidila et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
“…Two casecontrol studies (Kuvibidila et al, 1992;Merhav et al, 1985) focused on the relationship between tea consumption and the prevalence of anaemia without determining the iron deficiency status specifically with serum ferritin measurements. Both studies observed (Kuvibidila et al, 1992;Merhav et al, 1985) that anaemia, as determined by Tea consumption and iron status EHM Temme and PGA Van Hoydonck haemoglobin concentrations only, is more prevalent among tea drinking infants than among non-tea drinkers, even with a longer period of beef and poultry feeding in the tea group (Merhav et al, 1985) or adjusting for episodes of sickness (Kuvibidila et al, 1992). Differences in other dietary factors than tea were, however, not reported (Kuvibidila et al, 1992;Merhav et al, 1985) and the low weight suggested a lower total energy intake in tea drinkers in the Zairian study (Kuvibidila et al, 1992).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study of 120 infants aged 6 ± 12 months in Israel (Merhav et al, 1985) found that those who drank tea had a considerably higher frequency of anaemia (Hb`110 gal) than those who did not (64% vs 31%). This effect was not explicable by age or social class differences.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally it is thought to protect against diarrhoea. But some phenol compounds in tea are powerful inhibitors of iron absorption, sometimes up to 80% (19), which exacerbates iron deficiency in some infant and mother populations (20,21,22), especially if vitamin C intakes are low. Coffee and cola drinks can also inhibit iron absorption to varying degrees.…”
mentioning
confidence: 99%